Determinants of Interagency Communication in An Integrated Development Project - Dimbab, Ngidang; John, Fett (Universiti Malaysia Sarawak, (UNIMAS), 2001)
Planned development efforts have gradually shifted over the years from single issue rural development projects to integrated development projects. Planners have realised that most development problems do not stand in isolation, but require attention to a range of factors to bring about solutions. Because integrated developments projects simultaneously treat a broad range of development issues, they typically involve the efforts of numerous government agencies working in concert. They require some level of coordination and cooperation among these agencies if the projects are to reach their potential for success.